Widowhood stigma as a fundamental cause of poor mental, sexual, and reproductive health outcomes in sub-Saharan Africa: A conceptual framework - Jackline A. Odhiambo; Louisa N. Ndunyu; Erick O. Nyambedha; Ushma Upadhyay; Janet M. Turan; Elizabeth Bukusi; Nicodemus O. Agumba; Craig R. Cohen; Sheri D. Weiser (SSM - Mental Health)
Background: Widows in sub-Saharan Africa experience stigma linked to their social identity of widowhood. Despite the known significant impacts of stigma on health and wellbeing, widowhood stigma is less conceptualized and studied and its effects on widows' mental, sexual and reproductive health are not delineated. Methods: We thematically reviewed literature mentioning widowhood stigma and its effects in Africa. Applying the fundamental cause theory to this literature, we developed a widowhood stigma conceptual framework to highlight the domains of widowhood stigma and the pathways through which widowhood stigma impacts mental, sexual and reproductive health outcomes for widows. Results: We identified five domains of widowhood stigma: discriminatory socio-cultural and institutional norms, rituals, policies and laws, negative labelling and stereotyping, loss of social status, social isolation, and perceived, anticipated and internalized stigma. We show how widowhood stigma is a fundamental cause of poor mental, sexual and reproductive health outcomes through multiple pathways: distally through loss of material and social resources such as land disinheritance and lack of social support. Proximal pathways include health risk situations such as sexual exploitation and gender-based violence, maladaptive health and coping behaviors, and reduced access to health care. While several factors, such as a widows' age and educational level, might offer widows resources to resist stigma, other factors, such as intersectional stigma, might worsen the impact of widowhood stigma. Conclusion: Ours is likely the first framework focused on widowhood stigma in sub-Saharan Africa. This framework should assist in research on widowhood stigma and its health impacts, and in designing and evaluating interventions for reducing widowhood stigma and improving widows' health outcomes.